Income inequality and firearm homicide in the US: a county-level cohort study - Rowhani-Rahbar, Ali; Quistberg, Duane Alexander; Morgan, Erin R; Hajat, Anjum; Rivara, Frederick P (Injury prevention, 2019)
Income inequality has been rising in the US and thought to be associated with violence especially homicide. About 75% of homicides involve firearms. We quantified the association between county-level income inequality and all-race/ethnicity and race/ethnicity-specific firearm homicide rates among individuals aged 14-39 years. We conducted a cohort study of US counties to examine the association of Gini Index (ranging from 0 [perfect income equality] to 1.0 [perfect income inequality]) separately measured in 1990 and 2000 with all-race/ethnicity and race/ethnicity-specific firearm homicide rates in 2005-2015. Generalised linear mixed models with Poisson distribution including a random intercept for state provided IRRs and 95% CIs. Bayesian Poisson-lognormal hierarchical modelling with integrated nested Laplace approximations was used in exploratory spatial analyses. Models accounted for county-level age, sex and race/ethnicity composition, crime rate, deprivation, social capital, urbanicity, and firearm ownership. The Gini Index was associated with firearm homicide rates among all races/ethnicities. After accounting for contextual determinants of firearm homicide, the association persisted among African-Americans. In this group, a 1 SD greater Gini Index in 1990 (IRR=1.09; 95% CI 1.02 to 1.16) and 2000 (IRR=1.09; 95% CI 1.01 to 1.17) was associated with greater firearm homicide rates in 2005-2015. Exploratory spatial analyses did not materially change the results. Policies addressing the gap between the rich and the poor deserve further considerations for reducing firearm homicide rates. Incorporating income inequality to refine measures of socioeconomic position may advance public health and clinical research and practice for firearm violence prevention.